The Obstacles of Students and Teachers in Implementing The 2013 Revised Curriculum in Mathematics Learning: A Phenomenology Study - Ilmi, Sekar Ananda Nata Tiara; Ismunandar, Denni; Sudirman, Sudirman (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to examine and describe the obstacles faced by students in implementing the 2013 revised curriculum in 2018 in mathematics learning, as well as to examine and describe the obstacles faced by teachers in implementing the 2013 revised curriculum in 2018 in mathematics learning. The research instruments used in this study include data collection methods such as observation, in-depth interviews, and documentation. During the observation process, the researcher observes students and teachers during mathematics learning activities, while in-depth interviews are conducted to obtain interview results that will be analyzed using the ATLAS.ti 8 application, and documentation is carried out to capture images such as photos or videos during the observation and interview processes. Obstacles faced by students in implementing the 2013 revised curriculum in 2018 in mathematics learning include: students feeling less focused and concentrated during mathematics learning; students experiencing difficulties in understanding material, calculating, and memorizing mathematical formulas; incomplete and undetailed textbook content; the use of language in textbooks being too advanced; students often feeling sleepy during mathematics learning; students' mood affecting their learning activities; teachers not delivering the material in detail, too quickly, or too elaborately; classrooms being noisy; and inadequate facilities and infrastructure. Meanwhile, obstacles faced by teachers in implementing the 2013 revised curriculum in 2018 in mathematics learning include: language used by teachers being difficult for students to understand; low basic skills of students; students having different characteristics; students having low motivation and varying abilities.